2017
DOI: 10.1080/19390211.2016.1267062
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective and Anti-Inflammatory Effects ofPistacia atlanticaLeaf Hydroethanolic Extract Against Gentamicin-Induced Nephrotoxicity in Rats

Abstract: Gentamicin in overdose can lead to tubular injury and kidney dysfunction. Some antioxidants can protect kidneys against nephrotoxicity. This study was undertaken to evaluate the protective effects of Pistacia atlantica (P. atlantica) leaf hydroethanolic extract against gentamicin-induced nephrotoxicity in rats. Forty rats were divided into five groups: the first group received a daily intraperitoneal (i.p.) injection of normal saline. The second group received gentamicin (120 mg/kg, i.p.). The third, fourth, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…TNF‐α leads to oxidative stress which in turn increases the renal cells damage (Elmarakby & Sullivan, ; Ziamajidi, Nasiri, Abbasalipourkabir, & Sadeghi Moheb, ). Also, previous findings demonstrated that TNF‐α gene expression is elevated in renal damages (Heidarian et al, ; Valipour et al, ). In our research, administration of DIC caused an elevation in the renal expression of TNF‐α and its serum level (Figure ) which was accompanied with infiltration of lymphocytes in the renal section of DIC‐only‐treated group (Figure ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…TNF‐α leads to oxidative stress which in turn increases the renal cells damage (Elmarakby & Sullivan, ; Ziamajidi, Nasiri, Abbasalipourkabir, & Sadeghi Moheb, ). Also, previous findings demonstrated that TNF‐α gene expression is elevated in renal damages (Heidarian et al, ; Valipour et al, ). In our research, administration of DIC caused an elevation in the renal expression of TNF‐α and its serum level (Figure ) which was accompanied with infiltration of lymphocytes in the renal section of DIC‐only‐treated group (Figure ).…”
Section: Discussionmentioning
confidence: 86%
“…Produced ROS resulting from DIC can ruin lipids and proteins. Also, MDA and PC can result from protein oxidation and fatty acid peroxidation (Heidarian, Jafari‐Dehkordi, Valipour, Ghatreh‐Samani, & Ashrafi‐Eshkaftaki, ). In this study, administration of the DIC led to oxidative stress in the kidney which in turn causes nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, nephrotoxicity limits its use in clinical practice ( He et al, 2015 ). Doses of gentamicin ranging from 40–200 mg/kg administered for 4–10 d ( Bledsoe et al, 2008 ; Boroushaki et al, 2014 ; Heidarian et al, 2017 ; Jabbari et al, 2011 ) can induce acute renal failure in rats. Administration of 100 mg/kg i.p.…”
Section: Acute Kidney Injury Modelsmentioning
confidence: 99%
“…11 It has been shown that P. atlantica and its chemical factors induce some pharmacological actions including anticancer, antioxidant, anti-inflammatory, and antimicrobial activities. [12][13][14][15] Therefore, this project was initiated to evaluate the impact of long-term treatment with hydroalcoholic extract (HE) and essential oil (EO) of P. atlantica subsp. kurdica on glucose, lipid profile, TNF-α and oxidative stress biomarkers in streptozotocin (STZ)induced diabetic mice.…”
Section: Introductionmentioning
confidence: 99%